2017
DOI: 10.1021/acs.accounts.6b00579
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Characterization of Protein Adsorption onto Nanoparticles by Fluorescence Correlation Spectroscopy

Abstract: Nanotechnology holds great promise for applications in many fields including biology and medicine. Unfortunately, the processes occurring at the interface between nanomaterials and living systems are exceedingly complex and not yet well understood, which has significantly hampered the realization of many nanobiotechnology applications. Whenever nanoparticles (NPs) are incorporated by a living organism, a protein adsorption layer, also known as the "protein corona", forms on the NP surface. Accordingly, living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(142 citation statements)
references
References 72 publications
3
135
1
3
Order By: Relevance
“…As we will show further below, the excellent agreement of such data with a binding isotherm (Figure b) does not per se prove that a dynamic equilibrium rules the process . Thus, we checked for reversibility by measuring R H of the NPs immersed in PBS with specific Tf concentrations before and after eightfold dilution of the protein . R H decreased after dilution as predicted by the binding curve (Figure b), confirming reversibility of protein binding.…”
Section: Resultsmentioning
confidence: 99%
“…As we will show further below, the excellent agreement of such data with a binding isotherm (Figure b) does not per se prove that a dynamic equilibrium rules the process . Thus, we checked for reversibility by measuring R H of the NPs immersed in PBS with specific Tf concentrations before and after eightfold dilution of the protein . R H decreased after dilution as predicted by the binding curve (Figure b), confirming reversibility of protein binding.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that nanoparticles entering the body will combine with proteins to form complex due to excessive surface free energy. A large number of proteins attach to the surface of UFCB to form a protein corona (a protein membrane coated by proteins) . The combination of the two will change the function and structure of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of proteins attach to the surface of UFCB to form a protein corona (a protein membrane coated by proteins). [47][48][49] The combination of the two will change the function and structure of proteins.…”
Section: The Backbone Changes Of Bhb Induced By Ufcbmentioning
confidence: 99%
“…78 Materials in that environment, including but not limited to other nano-structures and various molecules (e.g., organic materials from lactose, plant or animal proteins and nucleic acids, dyes and/or minerals/ions in colloidal solutions with nano-structures), will attach (adsorb) to the outer surfaces of nano-scale structures to form new layers, coatings, or shells around the nano-structure. [78][79][80] Multiple factors, especially surface structure and surface energetics, as well as pH of the surrounding solution, 81 modulate the emergent properties of the resultant nanostructure coating. During the agitation such as sonication, vortexing, or manual succussions of a colloidal nano-structure solution, some of those elemental constituents, for example, nitrogen or phosphorus, as well as ethanol, may also dope the particles.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%